Effect of oral prednisolone on symptom duration and severity in nonasthmatic adults with acute lower respiratory tract infection: a randomized clinical trial - Hay, Alastair D.; Little, Paul; Harnden, Anthony; Thompson, Matthew; Wang, Kay; Kendrick, Denise; Orton, Elizabeth; Brookes, Sara T.; Young, Grace J.; May, Margaret; Hollinghurst, Sandra; Carroll, Fran E.; et al. (American Medical Association, 2017)
Importance: Acute lower respiratory tract infection is common and often treated inappropriately in primary care with antibiotics. Corticosteroids are increasingly used but without sufficient evidence. Objective: To assess the effects of oral corticosteroids for acute lower respiratory tract infection in adults without asthma. Design, Setting, and Participants: Multicenter, placebo-controlled, randomized trial (July 2013 to final follow-up October 2014) conducted in 54 family practices in England among 401 adults with acute cough and at least 1 lower respiratory tract symptom not requiring immediate antibiotic treatment and with no history of chronic pulmonary disease or use of asthma medication in the past 5 years. Interventions: Two 20-mg prednisolone tablets (n = 199) or matched placebo (n = 202) once daily for 5 days. Main Outcomes and Measures: The primary outcomes were duration of moderately bad or worse cough (0 to 28 days; minimal clinically important difference, 3.79 days) and mean severity of symptoms on days 2 to 4 (scored from 0 [not affected] to 6 [as bad as it could be]; minimal clinically important difference, 1.66 units). Secondary outcomes were duration and severity of acute lower respiratory tract infection symptoms, duration of abnormal peak flow, antibiotic use, and adverse events. Results: Among 401 randomized patients, 2 withdrew immediately after randomization, and 1 duplicate patient was identified. Among the 398 patients with baseline data (mean age, 47 [SD, 16.0] years; 63% women; 17% smokers; 77% phlegm; 70% shortness of breath; 47% wheezing; 46% chest pain; 42% abnormal peak flow), 334 (84%) provided cough duration and 369 (93%) symptom severity data. Median cough duration was 5 days (interquartile range [IQR], 3-8 days) in the prednisolone group and 5 days (IQR, 3-10 days) in the placebo group (adjusted hazard ratio, 1.11; 95% CI, 0.89-1.39; P = .36 at an α = .05). Mean symptom severity was 1.99 points in the prednisolone group and 2.16 points in the placebo group (adjusted difference, −0.20; 95% CI, −0.40 to 0.00; P = .05 at an α = .001). No significant treatment effects were observed for duration or severity of other acute lower respiratory tract infection symptoms, duration of abnormal peak flow, antibiotic use, or nonserious adverse events. There were no serious adverse events. Conclusions and Relevance: Oral corticosteroids should not be used for acute lower respiratory tract infection symptoms in adults without asthma because they do not reduce symptom duration or severity.